A review on columns used in chromatography - Badri, Sireesha; K, Shalini; A, Janaki; N, Sailaja; G, Ishwarya; M, Sai charan; D, Lokesh kumar (The Journal of Multidisciplinary Research, 2023)
Column chromatography is used extensively in nucleic acid chemistry to purify or characterize products from chemical reactions. This appendix focuses on separations using silica gel or alumina. The procedures described include loading the column, assembling the apparatus, separating compounds and collecting fractions, and optimizing chromatography conditions.Column chromatography issimple and the most popularseparation and purification technique. Column chromatography consists of a stationary solid phase that adsorbs and separates the compounds passing through it with the help of a liquid mobile phase. Various stationary phases, such as silica, alumina, calcium phosphate, calcium carbonate, starch, and magnesia, and different solvent compositions based on the nature of compounds to be separated and isolated, are used in column chromatography.